Dealings with God : from blasphemers in early modern Zurich to a cultural history of religiousness - Loetz, Francisca (Historian) (St. Andrews studies in Reformation history., 2009)
Blasphemy could be a serious business in early modern Europe, and those judged to have cursed, abused or denied God could in some cases find themselves on trial for their lives. Whilst such attitudes may appear draconian to modern eyes, it is clear that in the past, blasphemy was regarded as a very real threat to society. Concentrating on the Reformed city of Zurich, this study examines the cultural, social and theological aspects of blasphemy in order to better understand exactly why this should be, and to illuminate the diverse and sometimes contradictory dynamics at work.